Nursing diagnoses : definitions and classification 2024-2026 - Herdman, T. Heather; Kamitsuru, Shigemi; Takáo Lopes, Camila (Thieme, 2024)
In this new edition of a seminal text, the editors have provided a more in-depth discussion on diagnosis and its linkage to assessment, using Kamitsuru's Tripartite Model of Nursing Practice to differentiate between interdependent interventions based on medical and organizational standards of care, and autonomous nursing interventions based on nursing standards of care. Functional Health Patterns are used as an assessment framework to guide nurses in collecting relevant data to drive accuracy in nursing diagnosis. Ontology, classification and taxonomy are described, and the axial structure of our diagnoses - which has seen significant revision - is explained in detail. An overview on all changes and revisions in the classification is provided, along with updated research priorities and future foci for the Diagnosis Development Committee and the NANDA-I Association.